Reconstructing Islamic Marriage Law Based on Maqāṣid al-Sharī‘ah and Local Wisdom: A Study of the Uang Panai Tradition in Bugis-Makassar Culture - Akil, Muhammad; Syaripuddin, Said; Ardi, Ardi; Hasibuddin, M.; Surani, Surani (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2026)
Islamic marriage law in Indonesia continues to face challenges in reconciling universal religious principles with deeply rooted local customs. One such example is the uang panai tradition within Bugis-Makassar society, which often carries significant socio-economic implications beyond the scope of conventional Islamic mahr. This qualitative study applied a juridical-empirical method supported by theological-normative and anthropological approaches. Data were collected through document analysis, semi-structured interviews with religious leaders and cultural stakeholders, and field observations in Makassar, South Sulawesi. The findings reveal that uang panai, when framed within mutual consent and cultural appropriateness, aligns with key elements of maqāṣid al-sharī‘ah, notably the preservation of wealth (ḥifẓ al-māl), lineage (ḥifẓ al-nasl), and honour (ḥifẓ al-‘ird). The study highlights the flexibility of Islamic law through the legal maxim al-‘ādah muhakkamah, allowing cultural integration without compromising Sharī‘ah objectives. This research offers a conceptual model for reconstructing Islamic marriage law by integrating maqāṣid al-sharī‘ah with local traditions. The model promotes a dynamic and inclusive interpretation of Sharī‘ah that acknowledges cultural legitimacy while upholding Islamic legal integrity. It contributes to policy discourse on reforming Islamic family law in pluralistic societies